None Dare Call It Conspiracy - Allen G.; Abraham L.; Schmitz J. G. (Rossmoor Concord Press, 1972)
This book is a primer for anyone who wishes to understand the basic workings of the global network of Insiders that is determined to wield power over all of mankind in the coming New World Order. The Special Edition is updated with illustrations and charts for 2013. Introduction by U.S. Congressman John G. Schmitz: The story you are about to read is true. The names have not been changed to protect the guilty. This book may have the effect of changing your life. After reading this book, you will never look at national and world events in the same way again. None Dare Call It Conspiracy will be a very controversial book. At first it will receive little publicity and those whose plans are exposed in it will try to kill it by the silent treatment. For reasons that become obvious as you read this book, it will not be reviewed in all the "proper" places or be available on your local book stand. However, there is nothing these people can do to stop a grass roots book distributing system. Eventually it will be necessary for the people and organizations named in this book to try to blunt its effect by attacking it or the author. They have a tremendous vested interest in keeping you from discovering what they are doing. And they have the big guns of the mass media at their disposal to fire the barrages at None Dare Call It Conspiracy. By sheer volume, the "experts" will try to ridicule you out of investigating for yourself as to whether or not the information in this book is true They will ignore the fact that the author about to conjecture. They will find a typographical error or ague some point that is open to debate. If necessary they will lie in order to protect themselves by smearing this book. I believe those who pooh-pooh the information herein because psychologically many people would prefer to believe we are because we all like to ignore bad news. We do so at our own peril.
Keywords: 32